Koksidinia Kronis dengan Keterlibatan Sendi Facet - Hariyanto, Hori; Yahya, Corry Quando; Tantra, Andi Husni (Perdatin Pusat, 2014)
Koksidinia atau nyeri tulang ekor merupakan sebuah kondisi yang sering dicetuskan oleh subluksasi atau fraktur tulang coccyx. Akibatnya, inflamasi kronis akan menimbulkan nyeri yang sangat hebat pada daerah tersebut. Pada laporan kasus ini, kami menemukan gangguan sendi facet dalam menimbulkan koksidinia kronis. Meskipun literatur menyarankan coccygectomy pada penanganan kasus koksidinia kronik, ada baiknya jika Facet Block dipikirkan sebagai alternatif pengobatan nyeri sebelum beralih pada pembedahan. Laporan kasus ini membahas koksidinia kronis pada pasien wanita berusia 25 tahun dengan riwayat trauma. Terapi Ganglion Impar Block dengan 96% alkohol gagal dalam menghilangkan rasa nyeri. Blok dilakukan lagi dengan menggunakan 96% alkohol, bupivakain 0.25% and Triamcinolone, namun nyeri masih tetap dirasakan. Pasien tetap merasakan sulit untuk berjalan akibat nyeri, maka Facet blok pada L2–L4 kanan dilukakan dengan Radio Frequency (RF). Terapi tersebut menyebabkan nyeri tulang ekor menghilang secara permanen. Kasus ini menunjukkan bahwa nyeri muskuloskeletal kronik tidak berdiri sendiri, nyeri akan menyebabkan gangguan mobilisasi yang mengakibatkan perubahan pada otot, ligamen dan sendi sekitarnya. Kata kunci: Blok ganglion impar, koksidinia kronik, nyeri sendi facet Coccygodynia or tailbone pain is a chronic condition most commonly caused by subluxations and fractures of the coccyx. Intense pain is thought to arise from continuous inflammation within the coccygeal area. In this case report, we have discovered the development of lumbar facetogenic pain syndrome as a sequel to untreated chronic coccygodynia. Treatments should therefore be aimed at eliminating facet pain before resorting to operative procedures of the coccyx. In this report, we present the case of a 25 year old woman with chronic coccyx pain due to trauma. Ganglion Impar block had been given but failed to relieve the patient’s symptoms within one week post therapy. Blocks were later changed to 96% alcohol, bupivacaine 0.25% and Triamcinolone. Nevertheless, the pain continued to recur two weeks post-treatment. Due to presenting complaints of pain at standing and failure of blocks at the coccygeal level, facet blocks at L2-L4 was performed on the basis of lumbar facetogenic pain. This resulted in complete relief of symptoms including a 2 month follow-up report. Coccygodynia pain may not be a single disease entity. Intense chronic musculoskeletal pain will cause problems in mobilization thereby inflicting changes to the musculoskeletal, ligament and joint structures which may extend to other regions in the body. Key words: Chronic coccygodynia, facet joint pain, ganglion impar block Reference Fogel GR, Cunningham PY, Esses SI. Coccygodynia: Evaluation and Management. J am acad orthop surg. 2004;12(1):49 ̶ 54. Maigne JY, Chatellier G, Faou ML, Archambeau M. The treatment of chronic coccydynia with intrarectal manipulation: a randomized controlled study. Spine. 1976;31(18):E621 ̶ 7. Grgic V. Coccygodynia: etiology, pathogenesis, clinical characteristics, diagnosis and therapy. Lijec Vjesn. 2012;134(1-2):49 ̶ 55. Sehirlioglu A, Ozturk C, Oguz E, Emre T, Bek D, Altinmakas M. Coccygectomy in the surgical treatment of traumatic coccygodynia. Injury. 2007;38(2):182 ̶ 7. Mitra R, Cheung L, Perry P. Efficacy of fluoroscopically guided steroid injections in the management of coccydynia. Pain Physician. 2007;10(6):775 ̶ 8. Foye PM, Buttaci CJ, Stitik TP, Yonclas PP. Successful Injection for Coccyx Pain. Am J Phys Med Rehabil.2006;85(9):783 ̶ 410.1097/01.phm.0000233174.86070.63. Ianuzzi A, Little JS, Chiu JB, Baitner A, Kawchuk G, Khalsa PS. Human lumbar facet joint capsule strains: I. During physiological motions. Spine J. 2004;4(2):141 ̶ 52. Cavanaugh JM, Ozaktay AC, Yamashita HT, King AI. Lumbar facet pain: biomechanics, neuroanatomy and neurophysiology. J Biomech. 1996;29(9):1117 ̶ 29. Cohen SP, Raja SN. Pathogenesis, diagnosis, and treatment of lumbar zygapophysial (facet) joint pain. Anesthesiology. 2007;106(3):591 ̶ 614. Helbig T, Lee CK. The lumbar facet syndrome. Spine. 1976;13(1):61 ̶ 4.